Biogeochemical weathering of serpentinites: An examination of incipient dissolution affecting serpentine soil formation. (March 2015) - Baumeister, Julie L.; Hausrath, Elisabeth M.; Olsen, Amanda A.; Tschauner, Oliver; Adcock, Christopher T.; Metcalf, Rodney V.
Highlights: Dissolution of primary minerals is important to porosity generation in serpentinites. Mineral weathering extent in serpentinites follows the order Fe > Mg > Al rich minerals. Fe-oxidizing bacteria may mediate Fe-rich primary and serpentine mineral alteration. Serpentinite weathering is strongly impacted by degree of serpentinization. Abstract: Serpentinite rocks, high in Mg and trace elements including Ni, Cr, Cd, Co, Cu, and Mn and low in nutrients such as Ca, K, and P, form serpentine soils with similar chemical properties resulting in chemically extreme environments for the biota that grow upon them. The impact of parent material on soil characteristics is most important in young soils, and therefore the incipient weathering of serpentinite rock likely has a strong effect on the development of serpentine soils and ecosystems. Additionally, porosity generation is a crucial process in converting rock into a soil that can support vegetation. Here, the important factors affecting the incipient weathering of serpentinite rock are examined at two sites in the Klamath Mountains, California. Serpentinite-derived soils and serpentinite rock cores were collected in depth profiles from each sampling location. Mineral dissolution in weathered serpentinite samples, determined by scanning electron microscopy, energy dispersive spectrometry, electron microprobe analyses, and synchrotron microXRD, is consistent with the order, from most weathered to least weathered: Fe-rich pyroxene > antigorite > Mg-rich lizardite > Al-rich lizardite. These results suggest that the initial porosity formation within serpentinite rock, impacting the formation of serpentine soil on which vegetation can exist, is strongly affected both by the presence of non-serpentine primary minerals as well as the composition of the serpentine minerals. In particular, the presence of ferrous Fe appears to contribute to greater dissolution, whereas the presence of Al within the parent rock appears to contribute to greater stability. Iron-oxidizing bacteria present at the soil–rock interface have been shown in previous studies to contribute to the transition from rock to soil, and soils and rock cores in this study were therefore tested for iron-oxidizing bacteria. The detection of biological iron oxidation in this study indicates that the early alteration of these Fe-rich minerals may be mediated by iron-oxidizing bacteria. These findings help provide insight into the incipient processes affecting serpentinite rock weathering, important to the development of extreme serpentine soils and the biota that grow on them.